Talking with artists : conversations with Victoria Chess, Pat Cummings, Leo and Diane Dillon, Richard Egielski, Lois Ehlert, Lisa Campbell Ernst, Tom Feelings, Steven Kellogg, Jerry Pinkney, Amy Schwartz, Lane Smith, Chris Van Allsburg, and David Wiesner - Cummings, Pat. (New York : Bradbury Press ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1992)
Fourteen distinguished picture book artists talk about their early art experiences, answer questions most frequently asked by children, and offer encouragement to those who would like to become artists.
Includes bibliographical references (p. 93-95).
Children's Catalog (Wilson)
ALA Notable Books
SLJ Best Book
5.9
5-8
Keywords: Illustrators -- United States -- Biography -- Juvenile literature; Illustrators; Artists; Illustrators; Artists